1971
DOI: 10.1177/004051757104100707
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Flammability of Cotton, Polyester, and their Blends

Abstract: This study was undertaken to measure quantitatively the effect of temperature on the oxygen index values of several fabric samples of cotton, polyester, and their blends. The smoke density generated during the burning of these fabric samples at their oxygen indices was also studied at various temperature conditions. The results indicate a definite rela tionship of burning behavior with temperature, fabric weight, and composition of the blends. Two commercially avail able flame-retardant finishes were employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…P( 0) .CH,CH,.CO.N H .CH,OH, to raise the LO1 above 0.25 and possibly create 'selfextinguishing' behaviour. Obviously, the bromine influences the burning behaviour of polyester in the blend in a similar manner to that observed following the application of TH PC and 'tris' [395,404,430].…”
Section: Phosphorus-and Nitrogen-containing Systemssupporting
confidence: 60%
See 1 more Smart Citation
“…P( 0) .CH,CH,.CO.N H .CH,OH, to raise the LO1 above 0.25 and possibly create 'selfextinguishing' behaviour. Obviously, the bromine influences the burning behaviour of polyester in the blend in a similar manner to that observed following the application of TH PC and 'tris' [395,404,430].…”
Section: Phosphorus-and Nitrogen-containing Systemssupporting
confidence: 60%
“…The early blend studies of Tesoro and Meiser [390] and DiPietro et al [395,403] showed the need to render both components flame retardant in a polyester/cotton blend. However, even the use of the effective polyester flameretardant tris (2,3-dibromopropyl) phosphate in the presence of durably-retarded cotton (THPC) is very sensitive to blend composition and at 13% THPC and 11.5% 'tris' applied to cotton and polyester components, respectively, LO1 values fall from 0.361 for 100% cotton to 0.289 for a 35% cotton presence in the blend [395]. Whilst the use of 'tris' has proved to be an effective component in a combined finish treatment [404,405] and indeed, its effectiveness can be increased by partial acetylation of cotton present in the blend [406,407], its previously discussed toxicology [356] has prevented its successful application.…”
Section: Phosphorus-and Nitrogen-containing Systemsmentioning
confidence: 99%
“…*8 For a given fabric all these depend on the nature of the igniting source,29 the orientation of the fabric and location of ignition (top, bottom, edge, or face) and the environment conditions, With regard to the latter, not only are moisture10-12 and tempera--10. 13 important, but also whether still or forced-draught conditions preExtinguishability or the ease with which an ignited fabric is extinguished is a much less studied concept in spite of its lower dependence on certain of the above factors, in particular the character of the igniting source and mode of ignition. Miller et al15 initially considered the concept and measurement of extinguishability as a flammability criterion.…”
mentioning
confidence: 99%
“…The effects of temperature on the COI of fabrics have been investigated by a number of workers.38~ 459 48, 49 The effects can be complex, due in part to drying (which increases flammability) and to the chemical degradation of the fabric or any flame retardant component, but there is a tendency for the COI to decrease as temperature increases.…”
Section: Temperaturementioning
confidence: 99%